MeV He-4(++) channeling studies of epitaxially grown Pt films on Al2O3(0001) - Song, JH; Choi, WK; Kim, KH; Lee, JC; Kim, SC; Kim, HB; Lee, MH; Jeong, K; Whang, CN (ELSEVIER SCIENCE BV, 1999)
Crystallinity and structual properties of the epitaxially grown Pt films on Al2O3(0 0 0 1) substrate by RF magnetron sputtering at a substrate temperature of 600 degrees C were studied by using backscattering spectrometry (BS)/channeling and transmission electron microscopy (TEM) measurements. The Pt layer on Al2O3(0 0 0 1) substrate grew epitaxially to the direction of (1 1 1) with sixfold symmetry. Twin rotated by 180 degrees around Pt(1 1 1) axis was observed from the analysis of BS/channeling and TEM, In spite of the formation of twin in Pt film, the channeling minimum yield is as low as 4%. The result can be supported by the facts that (i) (1 1 1) direction of two kinds of Pt domain is parallel to each other and consistent with the direction of incident He-4 ions. (ii) Pt layer is only 180 degrees rotationally twinned at the twin boundary paralleled to the interface between Pt(1 1 1) and Al2O3(0 0 0 1) with same [1 1 1] axial channel. Therefore, incident He-4 ions do not experience dechanneling at the boundary of two domains. When the thickness of Pt film was less than 20 nm, a steep increase of the channeling minimum yield of Pt film was observed. It is suggested that when Pt him will be used as a buffer or seed layer for ferroelectric Pb(Zr,Ti)O-3(PZT) and GMR metals, the optimum thickness of Pt film kept with a good crystalline quality should be larger than 20 nm. (C) 1999 Elsevier Science B,V. All rights reserved.
Keywords: MAGNETIC-METAL STRUCTURES; BASAL-PLANE SAPPHIRE; GIANT MAGNETORESISTANCE